2019
DOI: 10.1001/jamanetworkopen.2019.2169
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Telephone Use and Reaction Time in Drivers With Glaucoma

Abstract: This cross-sectional study compares reaction times to peripheral stimuli while driving and using mobile telephones among patients with glaucoma vs healthy controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 33 publications
1
10
0
2
Order By: Relevance
“…Thus, the purpose of the present study is to examine how daily PA, age, and severity of visual impairment affects simple and complex visuomotor processing in patients with glaucoma. In accordance with previous findings [11,14,15], patients with glaucoma are hypothesized to achieve poorer scores in visuomotor processing tasks relative to those with no eye disease. Furthermore, in line with earlier studies [29][30][31][32], it is expected that severe visual field defects and lower PA levels will be associated with larger deficits in the executive functioning (as indicated by visuomotor task performance) of patients with glaucoma.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Thus, the purpose of the present study is to examine how daily PA, age, and severity of visual impairment affects simple and complex visuomotor processing in patients with glaucoma. In accordance with previous findings [11,14,15], patients with glaucoma are hypothesized to achieve poorer scores in visuomotor processing tasks relative to those with no eye disease. Furthermore, in line with earlier studies [29][30][31][32], it is expected that severe visual field defects and lower PA levels will be associated with larger deficits in the executive functioning (as indicated by visuomotor task performance) of patients with glaucoma.…”
Section: Introductionsupporting
confidence: 87%
“…Glaucomatous visual field loss may significantly affect functional daily living activities, in particular activities with heavy demands on visuomotor processing. Previous studies have found that glaucoma negatively affects gait and mobility [8][9][10], eye-hand coordination [11,12], and driving ability [13][14][15]. An increased risk of motor vehicle collisions has also been observed in glaucoma patients [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, fear of falling is the main reason many glaucoma patients avoid activities such as traveling out of town, walking, or venturing outside their home [8,9]. Furthermore, several studies showed a negative impact of glaucoma on physical and mental health including mobility [9,10], driving ability [11,12,13,14], reading [15], cognitive function [16,17,18], as well as processing speed and other abilities associated with complex yet instrumental activities of daily living [19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Por outro lado, dirigir de forma distraída limita o desempenho na direção devido à capacidade restrita do ser humano em dividir a atenção (46,61,67,68) (113,147) , razão que estimulou a realização deste estudo.…”
Section: Discussionunclassified
“…Sendo uma tarefa de alta demanda visual, a capacidade de dirigir pode ser significativamente comprometida em indivíduos com glaucoma (66)(67)(68) . Quando confrontados com o desafio adicional imposto pela atenção dividida devido ao uso do aparelho celular (147) , é possível que esses indivíduos possam ter uma redução ainda maior na capacidade de dirigir com segurança do que indivíduos saudáveis, particularmente em manter a atenção seletiva na mudança rápida de atenção, capacidade de rapidamente detectar estímulos periféricos e processar informações (84,92) , como identificado na fase II do estudo.…”
Section: Discussionunclassified